Micro- and Nanoplastic Exposure in Hospital Environments: A Scoping Review of Occupational Risks Among Healthcare Workers, with Particular Implications for Nursing - Otniel Alencar Bandeira; Lucas Barros de Araújo; Aline Franco da Rocha; Estefanía Coello Gonçalves Canedo; Vivian Vílchez Barboza; Weber da Silva Robazza; Gabriela Frutuozo Müller; Gilberto Costa Teodozio; Maria Lúcia do Carmo Cruz Robazzi (International Journal of Environmental Research and Public Health, 2026)
The extensive use of plastic-based materials in healthcare services has raised concerns about micro- and nanoplastic contamination in hospital environments, with potential implications for occupational health, environmental health, and public health nursing. This scoping review aimed to map the available evidence on occupational exposure to micro- and nanoplastics in healthcare settings, identifying exposure sources, pathways, potential health implications, and knowledge gaps, with particular attention to healthcare workers and nursing professionals. It was conducted following JBI methodology and reported according to PRISMA-ScR. Searches were performed in PubMed/MEDLINE, Scopus, Embase, LILACS, and SciELO for original studies published between January 2015 and December 2025 in English, Portuguese, or Spanish. Of 759 records identified, six studies met the eligibility criteria. Evidence was derived mainly from high-complexity healthcare settings, including operating theatres, anaesthetic rooms, laboratories, emergency departments, physiotherapy units, intensive care units, blood banks, and clinical areas. Indoor air, settled dust, disposable medical devices, plastic packaging, personal protective equipment, and plasticised materials were identified as potential exposure sources. Inhalation was the most frequently reported/inferred pathway, followed by dermal contact and indirect ingestion. Current evidence remains limited and heterogeneous, with scarce direct biomonitoring of micro- and nanoplastic particles and limited epidemiological data. Hospital environments may represent under-recognised settings for occupational exposure to micro- and nanoplastics, requiring standardised exposure assessment, environmental surveillance, biomonitoring, and preventive strategies aligned with occupational and public health nursing.